REPRESENTASI KESANTUNAN TINDAK TUTUR BERBAHASA INDONESIA DALAM PEMBELAJARAN DI KELAS (KAJIAN ETNOGRAFI KOMUNIKASI) - -, Syahrul R. (Diksi, 2015)
This article is about a research study conducted to describe and clarify politeness in speech acts using Indonesian in the talk done during a lesson in the classroom at SMA PMT Hamka, a senior high school in Padang Pariaman, Sumatra Barat, focusing on representations of (1) the forms of politeness in the speech acts, (2) the functions of politeness in the speech acts, and (3) the strategies of using politeness in the speech acts. It was a case study with communication ethnography and pragmatics as its starting points. The data consisted of two types: data from utterances and data from field notes. The two types of data, compiled by means of recordings, observations, and interviews, were analyzed with an interactive model of analysis. The research findings are as follows. First, in the context of representations of the forms of speech-act politeness, it is found that (a) such representations using Indonesian use the declarative, interrogative, and imperative modes, (b) the use of the declarative mode represents command, request, advice, and praise, (c) the use of the interrogative mode represents requesting, asking for what students have promised, clarifying whether students have understood, and giving a warning, (d) the use of the imperative mode represents invitation to do something, request, and command, (e) a softening of the illocution power is found in utterances using the declarative and interrogative modes so that the utterances are felt to be polite, (f) utterances using the interrogative mode, however, tends to have a strengthening effect on the illocution power so that the utterances are felt less polite. Second, in the context of representations of the functions of speech-act politeness, it is found that (a) the functions of politeness in directive acts consist of requesting, permitting, advising, commanding, and forbidding functions and (b) the functions of politeness in expressive acts consist of praising and thanking functions. Third, in the context of representations of the strategies of speech-act politeness, it is found that (a) utterances can be direct, realized in complete imperative form and imperative form with incomplete phrase and (b) utterances can be indirect by (1) being with expressions of politeness used in a positive way, (2) being with expressions of politeness used in a negative way, and (3) being unclear. Keywords: politeness, speech act, directive, expressive, classroom instruction 120